Online Attendance System Design to Reduce the Potential of Covid-19 Distribution: Online Attendance System Design to Reduce the Potential of Covid-19 Distribution - Nurhafni Rahayu; Fauziah Fauziah; Nur Hayati (Jurnal Mantik, 2020)
Amid the outbreak of the Covid-19 Virus, the attendance system of lecturers using finger print at the National University is very risky to facilitate the spread of Covid-19. With the old-time attendance system, of course will increase the touch by using the hands and fingers of lecturers on the same object. While it is known that the main spread of Covid-19 is through the media of hands and / or fingers. Under these conditions, a new and more sophisticated attendance system is needed to minimize the risk of the spread of Covid-19 at the National University. One such system is attendance online via a mobile phone.For this purpose, the authors plan to strike the Online Attendance system at the National University. Making this application using the Appsheet and can be used as an attendance machine, which validates attendance based on location with the integration of Global Positioning System (GPS) technology. The system automatically tracks the position of the lecturer whether in the campus area which has been determined by its coordinate points or vice versa, if not yet, the lecturer will still be allowed to make an absence or return absent using photo evidence that will be uploaded and fill in the information. All are stored in the Attendance Application event so that the lecturer can find out about attendance. Attendance by using this mobile system is expected to reduce the potential for the spread of Covid-19 at the National University when The New Normal is enforced.